Implementasi Program Magang Satu Data Indonesia dalam Penguatan Tata Kelola Data Transportasi di Dinas Perhubungan Provinsi Sumatera Selatan - Naufal Naufal (GLOBAL SCIENTS PUBLISHER, 2026)
The One Data Indonesia (Satu Data Indonesia) program is a strategic initiative by the government to realize integrated, accurate, up-to-date, and accessible data governance. This study aims to analyze the implementation of the One Data internship program at the Department of Transportation of South Sumatra Province, focusing on the process of data collection, verification, validation, and integration into the One Data dashboard. The research employs a descriptive qualitative approach with data collection through participatory observation, documentation studies, and structured interviews during the internship period from October 2024 to December 2025. The results indicate that the internship program successfully enhanced students' practical competencies in transportation data management, including data cleaning, format standardization, and metadata alignment. The program also contributed to strengthening the regional sectoral data ecosystem through systematic data governance support. However, several challenges were identified, including inconsistent data formats across Regional Government Organizations (OPD), limited system access in the early stages, and varying levels of data literacy among OPD staff. The study concludes that the One Data internship program provides significant benefits for both students and government institutions, and recommends early system access provision, cross-OPD data format standardization, and sustained student involvement to improve the quality and continuity of regional data governance.